Da’wa, Social Media and Challenge the Mainstream of Islam among Millennial Generation - Erwin Jusuf Thaib (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
This study aims to discuss the da’wa of Islam in relation to social media and how to challenge the mainstream of Islam among millennial generations in the community of Gorontalo City. The problem of this research is how the use of social media as a vehicle for da’wa for the millennial generation in Gorontalo City and what the challenges of da'wa for the millennial generation in Gorontalo City. This research uses qualitative methods, where data is obtained through observation, interviews and documentation studies. The findings of this study that social media can be used as a medium of da'wa especially for millennial generations. His da'wa material is the same as da'wa material in general, but the packaging follows the tastes of the millennial generation. Da'wa material on social media can be in the form of short narratives, pictures, or videos. Da'wa messages are delivered casually without patronizing. Nevertheless there are challenges of da’wa on social media for the millennial generation in the form of the spread of hoaxes behind religious messages and the lack of adequate capacity of the millennial generation to filter religious messages so that they absorb whatever they find on social media. In conclusion, social media can be an alternative medium of da'wa in the delivery of da'wa for the millennial generation. However, there must be literacy efforts in accepting and understanding religious messages in social media so that they are not trapped in the massive hoax trap of today.